Uranyl(VI) binding by bis(2-hydroxyaryl)diimine and bis(2-hydroxyaryl)diamine ligand derivatives. Synthetic, X-ray, DFT and solvent extraction studies. (8th January 2016) - Jeazet, Harold B. Tanh; Gloe, Kerstin; Doert, Thomas; Mizera, Jens; Kataeva, Olga N.; Tsushima, Satoru; Bernhard, Gert; Weigand, Jan J.; Lindoy, Leonard F.; Gloe, Karsten
Graphical abstract: Uranyl(VI) nitrate reacts with bis(2-hydroxyaryl)diimine and bis(2-hydroxyaryl)diamine ligand derivatives incorporating 1, 3-dimethylenebenzene or 1, 3-dimethylenecyclohexane bridges between nitrogen sites to yield unusual [UO2 (H2 L)(NO3 )2 ] complexes in which each H2 L only coordinates via its phenolic OH groups. In solvent extraction studies, clear uptake preference for UO 2 2 + over Eu 3+ was observed. Abstract: The interaction of uranyl(VI) nitrate with a series of bis(2-hydroxyaryl)imine (H2 L 1 –H2 L 5 ) and bis(2-hydroxyaryl)amine (H2 L 8, H2 L 9 ) derivatives incorporating 1, 3-dimethylenebenzene or 1, 3-dimethylenecyclohexane bridges between nitrogen sites is reported. Crystalline complexes of type [UO2 (H2 L)(NO3 )2 ] (where H2 L is H2 L 1 –H2 L 4 ) were isolated from methanol. X-ray structures of the complexes of H2 L 1, H2 L 2 and H2 L 4 show that each of these neutral ligands bind to their respective UO 2 2 + centres in a bidentate fashion in which coordination only occurs via each ligand's hydroxy functions. Two bidentate nitrate anions complete the metal's coordination sphere in each complex to yield hexagonal bipyramidal coordination geometries. A density functional theory (DFT) investigation of [UO2 (H2 L 1 )(NO3 )2 ] in a simulated methanol environment is in accord with this complex maintaining its solid state conformation in solution. Solvent extraction experiments (water/chloroform) employing H2 L 1 –H2 L 7 in the organic phase and uranyl(VI) nitrate in the aqueous phase showed that both amine derivatives, H2 L 8 and H2 L 9, yielded enhanced extraction of UO 2 2 + over the corresponding imine derivatives, H2 L 1 and H2 L 2 . These results were further compared with those obtained for the corresponding Schiff bases incorporating 1, 2-phenylene and 1, 2-cyclohexane bridged ligands, H2 L 6 and H2 L 7 ; these more rigid systems also yielded enhanced extraction of UO 2 2 + relative to the more flexible Schiff bases H2 L 1 –H2 L 5 . A very significant synergistic enhancement of the extraction of UO 2 2 + by H2 L 1 –H2 L 4 and H2 L 7 was observed in the presence of a 10-fold excess of n -octanoic acid; the influence of pH on extraction efficiency was also investigated. A parallel set of experiments employing H2 L 1 –H2 L 9 as extractants for europium(III) nitrate indicated a clear uptake preference for UO 2 2 + over Eu 3+ in all cases; separation of the uranyl ion from the rare earths is an important objective in mineral processing.